Movement-Based Interaction Applied to Physical Rehabilitation Therapies - Garrido Navarro, Juan Enrique; Ruiz Penichet, Victor Manuel; Lozano Pérez, María Dolores (JMIR Publications, 2014)
BackgroundHealth care environments are continuously improving conditions, especially regarding the use of current technology. In the field of rehabilitation, the use of video games and related technology has helped to develop new rehabilitation procedures. Patients are able to work on their disabilities through new processes that are more motivating and entertaining. However, these patients are required to leave their home environment to complete their rehabilitation programs. ObjectiveThe focus of our research interests is on finding a solution to eliminate the need for patients to interrupt their daily routines to attend rehabilitation therapy. We have developed an innovative system that allows patients with a balance disorder to perform a specific rehabilitation exercise at home. Additionally, the system features an assistive tool to complement the work of physiotherapists. Medical staff are thus provided with a system that avoids the need for them to be present during the exercise in specific cases in which patients are under suitable supervision. MethodsA movement-based interaction device was used to achieve a reliable system for monitoring rehabilitation exercises performed at home. The system accurately utilizes parameters previously defined by the specialist for correct performance of the exercise. Accordingly, the system gives instructions and corrects the patient's actions. The data generated during the session are collected for assessment by the specialist to adapt the difficulty of the exercise to the patient's progress. ResultsThe evaluation of the system was conducted by two experts in balance disorder rehabilitation. They were required to verify the effectiveness of the system, and they also facilitated the simulation of real patient behavior. They used the system freely for a period of time and provided interesting and optimistic feedback. First, they evaluated the system as a tool for real-life rehabilitation therapy. Second, their interaction with the system allowed us to obtain important feedback needed to improve the system. ConclusionsThe system improves the rehabilitation conditions of people with balance disorder. The main contribution comes from the fact that it allows patients to carry out the rehabilitation process at home under the supervision of physiotherapists. As a result, patients avoid having to attend medical centers. Additionally, medical staff have access to an assistant, which means their presence is not required in many exercises that involve constant repetition.